Association between microalbuminuria and serum Troponin-I in normotensive and nondiabetic patients with acute myocardial infarction; A cross-sectional analytical study - Amin, Md Al; Anwar, AFM Azim; Arzu, Jahanara; Safiuddin, Mohammad; Mahmood, Manzoor; Sheikh, Naveen; Abdullah, Abu Sadik; Salam, Md Abdus; Mahmud, Sohel; Rana, Masud; Hasan, Md Nazmul; Ahmed, Sheikh Foyez; et al. (University Heart Journal, 2025)
Background: Microalbuminuria (MA) happens more often in diabetic as well as hypertensive patients, but it has been recently reported that, MA can also be present in non–diabetic, normotensive patients with Acute MI (AMI). Serum Troponin-I sensitive and specific marker of AMI, but its costly, as well as, not widely available. This study was carried out to establish the correlation between serum Troponin-I and microalbuminuria in normotensive nondiabetic AMI population with normal renal function. Material and methods: This cross-sectional comparative observational study was carried out in the department of Cardiology, BSMMU, Dhaka Bangladesh to establish the correlation between microalbuminuria and serum troponin I. 50 non diabetic, normotensive patients of AMI and 50 healthy age and sex matched individuals were chosen. Microalbuminuria was determined by immunoturbidimetric method and plasma glucose were measured by enzymatic method. Result: There was significant(p<0.05) (pcorrelation between increased level of microalbuminuria with raised Troponin-I level, in patients with AMI, who were non diabetic and normotensive in comparison to those in the healthy individuals. Conclusion: Microalbuminuria has positive correlation with raised serum Troponin-I in AMI patients, in absence of traditional risk factors like diabetes and HTN. So, microalbuminuria can be used as a biochemical parameter in non-diabetic, normotensive AMI patients in poor resource settings. University Heart Journal 2024; 20(1): 10-13